Preparation method of high-performance acetabulum inner and outer lining integrated titanium-niobium-zirconium-tin medium-entropy alloy artificial hip joint prosthesis

By using microarc oxidation and microwave hydrothermal technology to prepare amorphous/crystal biphasic multilayer coating on the surface of artificial hip prosthesis, the problem of separation of acetabular inner and outer linings in the prior art is solved, the integration of the acetabular inner and outer linings is achieved, and the corrosion resistance and biological activity of the prosthesis are improved.

CN119732774APending Publication Date: 2025-04-01HARBIN INST OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411973788.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The acetabular lining and outer lining of existing artificial hip prostheses are separated, which is prone to fall off, resulting in failure of the operation.

Method used

A multi-layer coating consisting of amorphous/crystal biphasic and nanorods was prepared on the surface of the artificial hip prosthesis with microarctic oxidation combined with microwave hydrothermal technology to form a high-performance artificial hip prosthesis with integrated inner and outer lining of the acetabular bore.

Benefits of technology

Through microarc oxidation and microwave hydrothermal treatment, the corrosion resistance and biological activity of artificial hip prosthesis are significantly improved, and the problems of separation and easy fall off of the inner lining and outer lining are solved, and the integration of the inner and outer linings of the acetabular lining is achieved, and the service life of the prosthesis is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119732774A_ABST
    Figure CN119732774A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-performance acetabulum inner and outer lining integrated titanium-niobium-zirconium-tin medium-entropy alloy artificial hip joint prosthesis, and relates to a preparation method of an artificial hip joint prosthesis. The invention aims to solve the problems that an acetabulum inner lining and an acetabulum outer lining in an existing artificial hip joint prosthesis are separated and are easy to fall off, dislocation is generated, and an operation fails. The method comprises the following steps: 1, micro-arc oxidation treatment; and 2, microwave hydrothermal treatment. The method is used for preparing the high-performance acetabulum inner and outer lining integrated titanium-niobium-zirconium-tin medium-entropy alloy artificial hip joint prosthesis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing an artificial hip joint prosthesis. Background Art

[0002] External factors such as car accidents and sports can cause hip injuries. Hip prosthesis replacement technology is the best way to solve the problem of hip injury or damage. In clinical applications, commonly used artificial hip prosthesis materials are titanium and its alloys, but the hip joint is often in a complex stress state and complex physiological environment, which requires artificial hip prosthesis materials to have high strength, low modulus and excellent corrosion resistance. However, the acetabular liner and outer liner currently used in clinical practice are separate and assembled for use, but they are easy to fall off and dislocate, resulting in surgical failure. Therefore, it is urgent to develop a new technology of micro-arc oxidation combined with microwave hydrothermal to prepare amorphous / crystalline two-phase multilayer coatings on the surface of titanium-niobium-zirconium-tin medium entropy alloy artificial hip prosthesis in situ. Summary of the invention

[0003] The present invention aims to solve the problem that the acetabulum liner and the outer liner are separated and easily fall off in the existing artificial hip joint prosthesis, resulting in dislocation and leading to surgical failure, and further provides a method for preparing a high-performance acetabulum inner and outer liner integrated titanium niobium zirconium tin medium entropy alloy artificial hip joint prosthesis.

[0004] A method for preparing a high-performance acetabular inner and outer liner integrated titanium-niobium-zirconium-tin medium-entropy alloy artificial hip joint prosthesis is carried out according to the following steps:

[0005] 1. Micro-arc oxidation treatment:

[0006] The titanium, niobium, zirconium, and tin medium-entropy alloy hip joint prosthesis is placed in an electrolyte containing a bioactive component, the titanium, niobium, zirconium, and tin medium-entropy alloy hip joint prosthesis is used as an anode, and a stainless steel plate is used as a cathode. A constant current mode is adopted, and micro-arc oxidation is performed under the conditions of a current of 0.2A to 2.5A, a pulse frequency of 600Hz to 1000Hz, a duty cycle of 4% to 20%, and an electrolyte temperature of 20°C to 30°C to obtain a titanium, niobium, zirconium, and tin medium-entropy alloy hip joint prosthesis after micro-arc oxidation treatment;

[0007] The titanium-niobium-zirconium-tin medium-entropy alloy hip joint prosthesis is a femoral head prosthesis and an acetabulum prosthesis;

[0008] 2. Microwave hydrothermal treatment:

[0009] The titanium niobium zirconium tin medium-entropy alloy hip joint prosthesis after micro-arc oxidation treatment is immersed in alkaline solution and subjected to microwave hydrothermal treatment under the conditions of microwave hydrothermal temperature of 160℃~260℃ and microwave heating power of 500W~1000W. The surfaces of the femoral head prosthesis and the acetabular prosthesis are covered with a multilayer coating composed of amorphous / crystalline dual phase and nanorods. Finally, the coated femoral head prosthesis and the coated acetabular prosthesis are assembled to complete the preparation method of the titanium niobium zirconium tin medium-entropy alloy artificial hip joint prosthesis with integrated inner and outer liners of the high-performance acetabular liner.

[0010] The beneficial effects of the present invention are:

[0011] The present invention aims to develop a new type of artificial hip joint prosthesis with high-performance titanium-niobium-zirconium-tin medium-entropy alloy integrating inner and outer liners of acetabulum, and prepares a multilayer coating composed of amorphous / crystalline dual phase and nanorods on the surface of the femoral head in the artificial hip joint by micro-arc oxidation combined with microwave hydrothermal technology; prepares a multilayer coating composed of amorphous / crystalline dual phase and nanorods on the surface of the acetabulum by micro-arc oxidation combined with microwave hydrothermal technology to form an inner lining, and assembles the femoral head prosthesis and the acetabulum with integrated inner and outer liners to form a movable friction interface of soft-soft contact surface, thereby solving the problems of separation, easy falling off, and dislocation of the inner and outer liner (acetabulum) due to movement.

[0012] Specifically, an amorphous / crystalline dual-phase coating containing titanium, niobium, zirconium, tin, calcium and phosphorus elements is formed on the surface of the femoral head prosthesis by micro-arc oxidation technology, and the calcium and phosphorus elements exist in an amorphous state. In addition, the calcium-phosphorus micro-arc oxidation coating is treated with microwave hydrothermal treatment. The microwave hydrothermal treatment can significantly reduce the loss of active calcium and phosphorus elements in the coating, and at the same time, promote the conversion of the calcium-phosphorus amorphous phase into highly active zinc-doped hydroxyapatite nanorods, thereby improving the biological activity of the femoral stem in the artificial hip joint prosthesis, thereby realizing a high-performance multilayer coating with dual functions of high activity and high corrosion resistance, and obtaining a new type of artificial hip joint with integrated high-performance inner and outer linings of the hip joint, expanding the application of titanium, niobium, zirconium and tin medium-entropy alloys in hip joint injury repair.

[0013] The sample treated by the present invention was subjected to EDS spectrum detection, and the coating contained elements such as calcium, phosphorus, and zinc; after the treated sample was subjected to transmission electron microscopy detection, the coating was a multilayer coating composed of amorphous / crystalline, and the electrochemical polarization curve corrosion performance test showed that the corrosion resistance of the amorphous / crystalline dual-phase multilayer coating was significantly improved. XRD diffraction detection showed that the treated sample had an amorphous phase, anatase and zinc-doped hydroxyapatite. Scanning electron microscopy showed that a large number of zinc-doped hydroxyapatite nanorods were formed on the surface of the coating, with a length of about 1 μm and a diameter of about 100 nm. The surface of the treated sample was characterized for its apatite induction ability in vitro, and a large number of apatite structures were formed on the surface after being immersed in simulated body fluid for 2 days or more. It shows that the new artificial hip joint prosthesis in the present invention has higher corrosion resistance and apatite induction ability after micro-arc oxidation combined with microwave hydrothermal treatment.

[0014] Instruction Manual

[0015] Figure 1 Electrochemical corrosion curves of multilayer coatings composed of amorphous / crystalline dual phases and nanorods prepared in Example 2 and comparative experiments, MAOed TNZAMEA is Example 2, and MAOed Ti is comparative experiments;

[0016] Figure 2 XRD spectrum of the multilayer coating composed of amorphous / crystalline dual phase and nanorods prepared in Example 2, A is anatase peak, B is titanium peak (βTi, αTi), C is hydroxyapatite peak, and D is amorphous peak;

[0017] Figure 3 This is a scanned photo of a multilayer coating composed of an amorphous / crystalline dual phase and nanorods prepared in Example 2;

[0018] Figure 4 This is a transmission photograph of a multilayer coating composed of an amorphous / crystalline dual phase and nanorods prepared in Example 2;

[0019] Figure 5 This is an EDS spectrum of a multilayer coating composed of an amorphous / crystalline dual phase and nanorods prepared in Example 2;

[0020] Figure 6 This is a scanning photograph of the plate prepared in Example 2, which is covered with a multilayer coating consisting of an amorphous / crystalline dual phase and nanorods after being immersed in simulated body fluid for 5 days. DETAILED DESCRIPTION

[0021] Specific implementation method 1: This implementation method is a method for preparing a high-performance titanium-niobium-zirconium-tin medium-entropy alloy artificial hip joint prosthesis with integrated inner and outer linings of the acetabulum, which is carried out in the following steps:

[0022] 1. Micro-arc oxidation treatment:

[0023] The titanium, niobium, zirconium, and tin medium-entropy alloy hip joint prosthesis is placed in an electrolyte containing a bioactive component, the titanium, niobium, zirconium, and tin medium-entropy alloy hip joint prosthesis is used as an anode, and a stainless steel plate is used as a cathode. A constant current mode is adopted, and micro-arc oxidation is performed under the conditions of a current of 0.2A to 2.5A, a pulse frequency of 600Hz to 1000Hz, a duty cycle of 4% to 20%, and an electrolyte temperature of 20°C to 30°C to obtain a titanium, niobium, zirconium, and tin medium-entropy alloy hip joint prosthesis after micro-arc oxidation treatment;

[0024] The titanium-niobium-zirconium-tin medium-entropy alloy hip joint prosthesis is a femoral head prosthesis and an acetabulum prosthesis;

[0025] 2. Microwave hydrothermal treatment:

[0026] The titanium niobium zirconium tin medium-entropy alloy hip joint prosthesis after micro-arc oxidation treatment is immersed in alkaline solution and subjected to microwave hydrothermal treatment under the conditions of microwave hydrothermal temperature of 160℃~260℃ and microwave heating power of 500W~1000W. The surfaces of the femoral head prosthesis and the acetabular prosthesis are covered with a multilayer coating composed of amorphous / crystalline dual phase and nanorods. Finally, the coated femoral head prosthesis and the coated acetabular prosthesis are assembled to complete the preparation method of the titanium niobium zirconium tin medium-entropy alloy artificial hip joint prosthesis with integrated inner and outer liners of the high-performance acetabular liner.

[0027] The beneficial effects of this embodiment are:

[0028] This embodiment aims to develop a new type of artificial hip joint prosthesis made of titanium-niobium-zirconium-tin medium-entropy alloy with high-performance integrated inner and outer liners of the acetabulum. Micro-arc oxidation combined with microwave hydrothermal technology is used to prepare a multilayer coating composed of amorphous / crystalline dual phase and nanorods on the surface of the femoral head in the artificial hip joint; micro-arc oxidation combined with microwave hydrothermal technology is used to prepare a multilayer coating composed of amorphous / crystalline dual phase and nanorods on the surface of the acetabulum to form an inner lining, and the femoral head prosthesis and the acetabulum with integrated inner and outer liners are assembled to form a movable friction interface of a soft-soft contact surface, thereby solving the problems of separation, easy falling off, and dislocation of the inner and outer liner (acetabulum) due to movement.

[0029] Specifically, an amorphous / crystalline dual-phase coating containing titanium, niobium, zirconium, tin, calcium and phosphorus elements is formed on the surface of the femoral head prosthesis by micro-arc oxidation technology, and the calcium and phosphorus elements exist in an amorphous state. In addition, the calcium-phosphorus micro-arc oxidation coating is treated with microwave hydrothermal treatment. The microwave hydrothermal treatment can significantly reduce the loss of active calcium and phosphorus elements in the coating, and at the same time, promote the conversion of the calcium-phosphorus amorphous phase into highly active zinc-doped hydroxyapatite nanorods, thereby improving the biological activity of the femoral stem in the artificial hip joint prosthesis, thereby realizing a high-performance multilayer coating with dual functions of high activity and high corrosion resistance, and obtaining a new type of artificial hip joint with integrated high-performance inner and outer linings of the hip joint, expanding the application of titanium, niobium, zirconium and tin medium-entropy alloys in hip joint injury repair.

[0030] The samples treated by this embodiment were tested by EDS spectrum, and the coating contained elements such as calcium, phosphorus, and zinc; after the treated samples were tested by transmission electron microscopy, the coating was a multilayer coating composed of amorphous / crystalline, and the corrosion performance test of the electrochemical polarization curve showed that the corrosion resistance of the amorphous / crystalline dual-phase multilayer coating was significantly improved. XRD diffraction detection showed that the treated samples had amorphous phase, rutile, and zinc-doped hydroxyapatite. Scanning electron microscopy showed that a large number of zinc-doped hydroxyapatite nanorods were formed on the surface of the coating, with a length of about 1 μm and a diameter of about 100 nm. The surface of the treated sample was characterized for its apatite induction ability in vitro, and a large number of apatite structures were formed on the surface after being immersed in simulated body fluids for 2 days or more. It shows that the new artificial hip prosthesis in this embodiment has higher corrosion resistance and apatite induction ability after micro-arc oxidation combined with microwave hydrothermal treatment.

[0031] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the material of the titanium, niobium, zirconium, tin medium entropy alloy hip joint prosthesis described in step 1 is an equimolar titanium, niobium, zirconium, tin medium entropy alloy or a non-equimolar titanium, niobium, zirconium, tin medium entropy alloy. The rest is the same as specific embodiment 1.

[0032] Specific embodiment three: This embodiment is different from specific embodiment one or two in that the material of the titanium-niobium-zirconium-tin medium-entropy alloy hip joint prosthesis described in step one is a titanium-rich titanium-niobium-zirconium-tin medium-entropy alloy, and the titanium-rich titanium-niobium-zirconium-tin medium-entropy alloy is specifically prepared according to the following steps: 15at% to 30at% of niobium powder, 3at% to 10at% of zirconium powder, 4at% to 10at% of tin powder and the remainder of titanium powder are weighed according to atomic percentage, and then mixed evenly and placed in a vacuum arc melting furnace, and the temperature of the arc melting furnace is 2500℃ to 3000℃, and the vacuum degree in the furnace is 2×10 -3 Pa~1×10 -4 Under the conditions of 0.04 Pa and a current of 450 mA to 500 mA, the smelting is repeated 5 to 7 times, and each smelting lasts 15 to 50 minutes. The rest is the same as the first or second specific implementation.

[0033] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that: the titanium niobium zirconium tin medium entropy alloy hip joint prosthesis described in step 1 is a pretreated titanium niobium zirconium tin medium entropy alloy hip joint prosthesis; the pretreatment is specifically carried out in the following steps: polishing the surface of the titanium niobium zirconium tin medium entropy alloy hip joint prosthesis with 400# and 1000# metallographic sandpaper in sequence, then washing with deionized water, and finally drying at a temperature of 20℃ to 30℃ for 0.5h to 1h. The rest is the same as specific embodiments 1 to 3.

[0034] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the electrolyte containing bioactive components in step 1 is a mixture of deionized water, disodium ethylenediaminetetraacetic acid, sodium hydroxide, sodium silicate, calcium dihydrogen phosphate and calcium acetate. The rest is the same as specific embodiments 1 to 4.

[0035] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that the concentration of disodium ethylenediaminetetraacetate in the electrolyte containing biologically active ingredients described in step 1 is 8 g / L to 20 g / L, the concentration of sodium hydroxide is 4 g / L to 15 g / L, the concentration of sodium silicate is 4 g / L to 15 g / L, the concentration of calcium dihydrogen phosphate is 5 g / L to 10 g / L, and the concentration of calcium acetate is 4 g / L to 10 g / L. Others are the same as specific embodiments 1 to 5.

[0036] Specific embodiment 7: This embodiment differs from Specific embodiments 1 to 6 in that: in step 1, micro-arc oxidation is performed for 10 min to 30 min under the conditions of a current of 0.2 A to 2.5 A, a pulse frequency of 600 Hz to 1000 Hz, a duty cycle of 4% to 20%, and an electrolyte temperature of 20° C. to 30° C. The rest is the same as Specific embodiments 1 to 6.

[0037] Specific implementation eight: This implementation differs from specific implementations one to seven in that the alkali solution in step two is sodium hydroxide solution, ammonia water or potassium hydroxide solution. The rest is the same as specific implementations one to seven.

[0038] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that the concentration of the alkali solution in step 2 is 0.01 mol / L to 3.0 mol / L. The rest is the same as specific embodiments 1 to 8.

[0039] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that in step 2, the microwave hydrothermal treatment is performed for 5 to 60 minutes under the conditions of a microwave hydrothermal temperature of 160° C. to 260° C. and a microwave heating power of 500 W to 1000 W. The rest is the same as specific embodiments 1 to 9.

[0040] The following examples are used to verify the beneficial effects of the present invention:

[0041] Embodiment 1:

[0042] A method for preparing a high-performance acetabular inner and outer liner integrated titanium-niobium-zirconium-tin medium-entropy alloy artificial hip joint prosthesis is carried out according to the following steps:

[0043] 1. Micro-arc oxidation treatment:

[0044] The titanium-niobium-zirconium-tin medium-entropy alloy hip prosthesis was placed in an electrolyte containing bioactive components, with the titanium-niobium-zirconium-tin medium-entropy alloy hip prosthesis as the anode and the stainless steel plate as the cathode. The micro-arc oxidation was performed for 10 minutes in a constant current mode at a current of 1.5A, a pulse frequency of 600Hz, a duty cycle of 8% and an electrolyte temperature of 25°C to obtain the titanium-niobium-zirconium-tin medium-entropy alloy hip prosthesis after micro-arc oxidation.

[0045] The titanium-niobium-zirconium-tin medium-entropy alloy hip joint prosthesis is a femoral head prosthesis and an acetabulum prosthesis;

[0046] 2. Microwave hydrothermal treatment:

[0047] The titanium, niobium, zirconium, and tin medium-entropy alloy hip joint prosthesis after micro-arc oxidation treatment was immersed in alkaline solution and subjected to microwave hydrothermal treatment for 10 minutes at a microwave hydrothermal temperature of 200°C and a microwave heating power of 800 W. The surfaces of the femoral head prosthesis and the acetabular prosthesis were covered with a multilayer coating composed of amorphous / crystalline dual phase and nanorods. Finally, the coated femoral head prosthesis and the coated acetabular prosthesis were assembled to complete the preparation method of a high-performance titanium, niobium, zirconium, and tin medium-entropy alloy artificial hip joint prosthesis with integrated inner and outer liners of the acetabulum.

[0048] The material of the titanium-niobium-zirconium-tin medium-entropy alloy hip joint prosthesis described in step 1 is a titanium-rich titanium-niobium-zirconium-tin medium-entropy alloy. The titanium-rich titanium-niobium-zirconium-tin medium-entropy alloy is specifically prepared according to the following steps: 15at% of niobium powder, 3at% of zirconium powder, 4at% of tin powder and 78at% of titanium powder are weighed according to atomic percentage, and then mixed evenly and placed in a vacuum arc melting furnace. The temperature of the arc melting furnace is 2500°C and the vacuum degree in the furnace is 2×10 -3 Under the conditions of 0.04 Pa and a current of 500 mA, the melting was repeated 5 times, and each melting was 30 minutes.

[0049] The titanium, niobium, zirconium, and tin medium-entropy alloy hip prosthesis described in step one is a pretreated titanium, niobium, zirconium, and tin medium-entropy alloy hip prosthesis; the pretreatment is specifically carried out according to the following steps: polishing the surface of the titanium, niobium, zirconium, and tin medium-entropy alloy hip prosthesis with 400# and 1000# metallographic sandpapers in turn, then washing it with deionized water, and finally drying it at a temperature of 20°C for 0.5h.

[0050] The electrolyte containing the bioactive component described in step 1 is prepared by mixing deionized water, disodium ethylenediaminetetraacetic acid, sodium hydroxide, sodium silicate, calcium dihydrogen phosphate and calcium acetate.

[0051] The concentration of disodium ethylenediaminetetraacetate in the electrolyte containing biologically active ingredients described in step 1 is 8 g / L, the concentration of sodium hydroxide is 15 g / L, the concentration of sodium silicate is 10 g / L, the concentration of monocalcium phosphate is 10 g / L, and the concentration of calcium acetate is 8 g / L.

[0052] The alkali solution described in step 2 is sodium hydroxide solution.

[0053] The concentration of the alkali solution described in step 2 is 0.5 mol / L.

[0054] Embodiment 2: This embodiment is different from Embodiment 1 in that: in order to carry out relevant test standards, the titanium-niobium-zirconium-tin medium-entropy alloy hip prosthesis described in step 1 is replaced with a titanium-niobium-zirconium-tin medium-entropy alloy plate having a size of 10 mm×10 mm×1 mm; in step 2, the surface of the plate is coated with a multilayer coating composed of an amorphous / crystalline dual phase and nanorods to obtain a coated plate. The rest is the same as in Embodiment 1.

[0055] Comparative experiment: This comparative experiment is different from Example 2 in that the material of the artificial hip joint prosthesis described in step 1 is titanium. The rest is the same as Example 2.

[0056] Figure 1 The electrochemical corrosion curves of the multilayer coating composed of amorphous / crystalline dual phase and nanorods prepared in Example 2 and the comparative experiment, MAOed TNZAMEA is Example 2, and MAOedTi is the comparative experiment. By comparing the electrochemical curves of the two, it can be clearly seen that the amorphous / crystalline dual phase high performance multilayer coating on the surface of the titanium niobium zirconium tin medium entropy alloy has a lower corrosion current (-5.875×10 -9 A / cm 2 ) and corrosion potential (-0.206V), indicating that the amorphous / crystalline dual-phase high-performance coating on the surface of Ti-Nb-Zr-Sn medium-entropy alloy has excellent corrosion resistance.

[0057] Figure 2 This is the XRD spectrum of the multilayer coating composed of an amorphous / crystalline dual phase and nanorods prepared in Example 2, where A is the anatase peak, B is the titanium peak (βTi, αTi), C is the hydroxyapatite peak, and D is the amorphous peak. It can be seen from the figure that anatase, amorphous structure and hydroxyapatite exist in the coating. At the same time, since no calcium-phosphorus-containing phase is detected in the XRD spectrum, it can be proved that the calcium-phosphorus element exists in an amorphous form.

[0058] Figure 3 This is a scanned photo of a multilayer coating composed of an amorphous / crystalline dual phase and nanorods prepared in Example 2; Figure 4 This is a transmission photograph of a multilayer coating composed of amorphous / crystalline dual phase and nanorods prepared in Example 2; from the scanning photograph, it can be seen that a large number of hydroxyapatite nanorods are formed on the surface of the coating, which are about 1 μm in length and about 100 nm in diameter. From the transmission photograph, it can be seen that after microwave hydrothermal treatment, a multilayer coating structure is obtained, including a substrate, a porous layer formed after treatment, and an epitaxial growth layer.

[0059] Figure 5This is the EDS spectrum of the multilayer coating composed of amorphous / crystalline dual phase and nanorods prepared in Example 2. As can be seen from the figure, the coating contains active elements such as calcium, phosphorus, niobium, titanium, tin and zirconium.

[0060] Figure 6 This is a scanning photograph of the plate prepared in Example 2, which is covered with a multilayer coating composed of an amorphous / crystalline dual phase and nanorods after being immersed in simulated body fluid for 5 days; as can be seen from the figure, a large amount of sediment is formed on the surface of the high-performance multilayer coating, and its surface feature presents a network structure of apatite, which has completely covered the surface of the sample, indicating that the sample has high biological activity.

[0061] Embodiment 3: This embodiment differs from Embodiment 2 in that in step 1, the micro-arc oxidation is performed for 10 minutes under the conditions of a current of 2.0 A, a pulse frequency of 600 Hz, a duty cycle of 8%, and an electrolyte temperature of 20° C. The rest is the same as Embodiment 2.

[0062] The amorphous / crystalline dual-phase high-performance multilayer coating obtained in this embodiment contains amorphous, anatase and hydroxyapatite. A large number of hydroxyapatite nanorods are formed on the surface of the amorphous / crystalline dual-phase high-performance multilayer coating. The coating contains active elements such as calcium, phosphorus, titanium, zirconium, tin and niobium, and has excellent corrosion resistance. After the amorphous / crystalline dual-phase high-performance multilayer coating was immersed in simulated body fluid for 3 days, a large amount of sediment was formed on the surface of the high-performance multilayer coating, and its surface characteristics showed a network structure of apatite, which completely covered the surface of the sample.

[0063] Example 4: This example is different from Example 2 in that: in step 2, the microwave hydrothermal treatment is performed for 60 minutes under the conditions of a microwave hydrothermal temperature of 220° C. and a microwave heating power of 800 W. The rest is the same as Example 2.

[0064] The amorphous / crystalline dual-phase high-performance multilayer coating obtained in this embodiment contains amorphous, anatase and hydroxyapatite. A large number of hydroxyapatite nanorods are formed on the surface of the amorphous / crystalline dual-phase high-performance multilayer coating. The coating contains active elements such as calcium, phosphorus, titanium, zirconium, tin and niobium, and has excellent corrosion resistance. After the amorphous / crystalline dual-phase high-performance multilayer coating was immersed in simulated body fluid for 2 days, a large amount of sediment was formed on the surface of the high-performance multilayer coating, and its surface characteristics showed a network structure of apatite, which completely covered the surface of the sample.

[0065] Embodiment 5: This embodiment differs from Embodiment 2 in that the concentration of the alkali solution in step 2 is 0.01 mol / L. The rest is the same as Embodiment 2.

[0066] The amorphous / crystalline dual-phase high-performance multilayer coating obtained in this embodiment contains amorphous, anatase and zinc-doped hydroxyapatite. A large number of zinc-doped hydroxyapatite nanorods are formed on the surface of the amorphous / crystalline dual-phase high-performance multilayer coating. The coating contains active elements such as calcium, phosphorus, titanium, zirconium, tin and niobium, and has excellent corrosion resistance. After the amorphous / crystalline dual-phase high-performance multilayer coating was immersed in simulated body fluid for 5 days, a large amount of sediment was formed on the surface of the high-performance multilayer coating, and its surface characteristics showed a network structure of apatite, which completely covered the surface of the sample.

[0067] Embodiment 6: This embodiment is different from Embodiment 2 in that the concentration of the alkali solution in step 2 is 1.0 mol / L. The rest is the same as Embodiment 2.

[0068] The amorphous / crystalline dual-phase high-performance multilayer coating obtained in this embodiment contains amorphous, anatase and hydroxyapatite. A large number of hydroxyapatite nanorods are formed on the surface of the amorphous / crystalline dual-phase high-performance multilayer coating. The coating contains active elements such as calcium, phosphorus, titanium, zirconium, tin and niobium, and has excellent corrosion resistance. After the amorphous / crystalline dual-phase high-performance multilayer coating was immersed in simulated body fluid for 5 days, a large amount of sediment was formed on the surface of the high-performance multilayer coating, and its surface characteristics showed a network structure of apatite, which completely covered the surface of the sample.

[0069] Embodiment 7: This embodiment is different from Embodiment 2 in that the concentration of the alkali solution in step 2 is 3.0 mol / L. The rest is the same as Embodiment 2.

[0070] The amorphous / crystalline dual-phase high-performance multilayer coating obtained in this embodiment contains amorphous, anatase and hydroxyapatite. A large number of hydroxyapatite nanorods are formed on the surface of the amorphous / crystalline dual-phase high-performance multilayer coating. The coating contains active elements such as calcium, phosphorus, titanium, zirconium, tin and niobium, and has excellent corrosion resistance. After the amorphous / crystalline dual-phase high-performance multilayer coating was immersed in simulated body fluid for 7 days, a large amount of sediment was formed on the surface of the high-performance multilayer coating, and its surface characteristics showed a network structure of apatite, which completely covered the surface of the sample.

[0071] The contents of the simulated body fluid components described in Examples 2 to 7 are shown in Table 1

[0072] Table 1 Chemical reagent content of 1L simulated body fluid

[0073]

Claims

1. A method for preparing a high-performance acetabular inner and outer liner integrated titanium-niobium-zirconium-tin medium-entropy alloy artificial hip joint prosthesis, characterized in that It is carried out in the following steps:

1. Micro-arc oxidation treatment: The titanium, niobium, zirconium, and tin medium-entropy alloy hip joint prosthesis is placed in an electrolyte containing a bioactive component, the titanium, niobium, zirconium, and tin medium-entropy alloy hip joint prosthesis is used as an anode, and a stainless steel plate is used as a cathode. A constant current mode is adopted, and micro-arc oxidation is performed under the conditions of a current of 0.2A to 2.5A, a pulse frequency of 600Hz to 1000Hz, a duty cycle of 4% to 20%, and an electrolyte temperature of 20°C to 30°C to obtain a titanium, niobium, zirconium, and tin medium-entropy alloy hip joint prosthesis after micro-arc oxidation treatment; The titanium-niobium-zirconium-tin medium-entropy alloy hip joint prosthesis is a femoral head prosthesis and an acetabulum prosthesis; 2. Microwave hydrothermal treatment: The titanium niobium zirconium tin medium-entropy alloy hip joint prosthesis after micro-arc oxidation treatment is immersed in alkaline solution and subjected to microwave hydrothermal treatment under the conditions of microwave hydrothermal temperature of 160℃~260℃ and microwave heating power of 500W~1000W. The surfaces of the femoral head prosthesis and the acetabular prosthesis are covered with a multilayer coating composed of amorphous / crystalline dual phase and nanorods. Finally, the coated femoral head prosthesis and the coated acetabular prosthesis are assembled to complete the preparation method of the titanium niobium zirconium tin medium-entropy alloy artificial hip joint prosthesis with integrated inner and outer liners of the high-performance acetabular liner.

2. The method for preparing a high-performance acetabular inner and outer liner integrated titanium-niobium-zirconium-tin medium-entropy alloy artificial hip joint prosthesis according to claim 1, characterized in that The material of the titanium, niobium, zirconium, and tin medium-entropy alloy hip joint prosthesis described in step 1 is an equimolar titanium, niobium, zirconium, and tin medium-entropy alloy or a non-equimolar titanium, niobium, zirconium, and tin medium-entropy alloy.

3. The method for preparing a high-performance acetabular inner and outer liner integrated titanium-niobium-zirconium-tin medium-entropy alloy artificial hip joint prosthesis according to claim 2, characterized in that The material of the titanium-niobium-zirconium-tin medium-entropy alloy hip joint prosthesis described in step 1 is a titanium-rich titanium-niobium-zirconium-tin medium-entropy alloy. The titanium-rich titanium-niobium-zirconium-tin medium-entropy alloy is specifically prepared according to the following steps: 15at% to 30at% of niobium powder, 3at% to 10at% of zirconium powder, 4at% to 10at% of tin powder and the remainder of titanium powder are weighed according to atomic percentage, and then mixed evenly and placed in a vacuum arc melting furnace. The temperature of the arc melting furnace is 2500°C to 3000°C and the vacuum degree in the furnace is 2×10 -3 Pa~1×10 -4 Under the conditions of Pa and current of 450mA to 500mA, the smelting is repeated 5 to 7 times, and each smelting lasts 15min to 50min.

4. The method for preparing a high-performance acetabular inner and outer liner integrated titanium-niobium-zirconium-tin medium-entropy alloy artificial hip joint prosthesis according to claim 1, characterized in that The titanium, niobium, zirconium, and tin medium-entropy alloy hip prosthesis described in step one is a pretreated titanium, niobium, zirconium, and tin medium-entropy alloy hip prosthesis; the pretreatment is specifically carried out according to the following steps: polishing the surface of the titanium, niobium, zirconium, and tin medium-entropy alloy hip prosthesis with 400# and 1000# metallographic sandpaper in sequence, then washing it with deionized water, and finally drying it at a temperature of 20°C to 30°C for 0.5h to 1h.

5. The method for preparing a high-performance acetabular inner and outer liner integrated titanium-niobium-zirconium-tin medium-entropy alloy artificial hip joint prosthesis according to claim 1, characterized in that The electrolyte containing the bioactive component described in step 1 is prepared by mixing deionized water, disodium ethylenediaminetetraacetic acid, sodium hydroxide, sodium silicate, calcium dihydrogen phosphate and calcium acetate.

6. The method for preparing a high-performance acetabular inner and outer liner integrated titanium-niobium-zirconium-tin medium-entropy alloy artificial hip joint prosthesis according to claim 5, characterized in that The concentration of disodium edetate in the electrolyte containing biologically active ingredients described in step 1 is 8 g / L to 20 g / L, the concentration of sodium hydroxide is 4 g / L to 15 g / L, the concentration of sodium silicate is 4 g / L to 15 g / L, the concentration of monocalcium phosphate is 5 g / L to 10 g / L, and the concentration of calcium acetate is 4 g / L to 10 g / L.

7. The method for preparing a high-performance acetabular inner and outer liner integrated titanium-niobium-zirconium-tin medium-entropy alloy artificial hip joint prosthesis according to claim 1, characterized in that In step 1, micro-arc oxidation is performed for 10 min to 30 min under the conditions of a current of 0.2 A to 2.5 A, a pulse frequency of 600 Hz to 1000 Hz, a duty cycle of 4% to 20% and an electrolyte temperature of 20° C. to 30° C.

8. The method for preparing a high-performance acetabular inner and outer liner integrated titanium-niobium-zirconium-tin medium-entropy alloy artificial hip joint prosthesis according to claim 1, characterized in that The alkali solution described in step 2 is sodium hydroxide solution, ammonia water or potassium hydroxide solution.

9. The method for preparing a high-performance acetabular inner and outer liner integrated titanium-niobium-zirconium-tin medium-entropy alloy artificial hip joint prosthesis according to claim 8, characterized in that The concentration of the alkali solution described in step 2 is 0.01 mol / L to 3.0 mol / L.

10. The method for preparing a high-performance acetabular inner and outer liner integrated titanium-niobium-zirconium-tin medium-entropy alloy artificial hip joint prosthesis according to claim 1, characterized in that In step 2, the microwave hydrothermal treatment is carried out for 5 min to 60 min under the conditions of a microwave hydrothermal temperature of 160° C. to 260° C. and a microwave heating power of 500 W to 1000 W.

Citation Information

Patent Citations

  • TiZrNb hip joint prosthesis and production method thereof

    CN103110982A

  • Method for constructing hydroxyapatite-containing high-performance multilayer coating with antibacterial and osteogenic effects on surface of titanium implant

    CN116747351A

  • Artificial joint surface zinc oxide doped bionic coating and preparation method thereof

    CN116791171A

  • (Ta, Nb, Hfx) 2C medium-entropy alloyed carbide ceramic and preparation method thereof

    CN117024147A

  • (Ti-Zr-Nb-Ta)-Ga series high / medium entropy alloy and preparation method and application thereof

    CN118835145A